Implementasi Routing Berbasis Algoritme Dijkstra Pada Software Defined Networking Menggunakan Kontroler Open Network Operating System - Faizal Ramadhan; Rakhmadhany Primananda; Widhi Yahya (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Software Defined Networking is a new paradigm that emerging in networking industry to solve today's computer network problem such as the difficult configuration because it used low-level configuration as well as limited visual devices. By using the SDN network, the network will have advantages such as easy to developing and experimenting of new protocols, easy to manage, and ease the network to adapt when there is infrastructure changes. Controller is an important part of the SDN network, because the controller has function to control the login in SDN network. ONOS is a controller that offers the advantage delivering high-availablity, scalable, and bring performace as good as carrier grade class. Dijkstra's shortest path algorithm is one of the routing algorithms. Dijkstra's shortest path routing performance on SDN network using ONOS controller produces lantecy time 0,092 ms using geoDistance function and latency time 0,097 using linkMetric function. This concluded latency time will increase along with the lenght the path used for communicate between hosts. Meanwhile the performance test result of ONOS controller while running Dijkstra algorithm as well as responding to fail path on the network link resulted that ONOS controller provide good performance on the network that requires infrastructure with combination of 20 switches and 40 hosts, and the average convergence time that ONOS needed to build new path is 1,405s.